Institutional Investors and Concentration of Financial Power: Berle and Means Revisted: Discussion - Tinic, S. M. (Journal of Finance, 1981)
S. M. Tinic, Institutional Investors and Concentration of Financial Power: Berle and Means Revisted: Discussion, The Journal of Finance, Vol. 36, No. 2, Papers and Proceedings of the Thirty Ninth Annual Meeting American Finance Association, Denver, September 5-7, 1980 (May, 1981), pp. 395-397